Artificial neural networks for computer-aided modelling and optimisation in micellar electrokinetic chromatography - Havel, J; Breadmore, M; Macka, M; Haddad, P R (Journal of chromatography. A, 1999)
The separation process in capillary micellar electrochromatography (MEKC) can be modelled using artificial neural networks (ANNs) and optimisation of MEKC methods can be facilitated by combining ANNs with experimental design. ANNs have shown attractive possibilities for non-linear modelling of response surfaces in MEKC and it was demonstrated that by combining ANN modelling with experimental design, the number of experiments necessary to search and find optimal separation conditions can be reduced significantly. A new general approach for computer-aided optimisation in MEKC has been proposed which, because of its general validity, can also be applied in other separation techniques.
Keywords: Computer Simulation; neuronové sítě; Research Design; Edetic Acid; počítačová simulace; Chromatography, Micellar Electrokinetic Capillary; Neural Networks, Computer; EDTA; kovy; Metals; chromatografie micelární elektrokinetická kapilární; výzkumný projekt